2019
DOI: 10.1155/2019/8602562
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Silicone Oil on Dispersion and Low-Temperature Fracture Performance of Crumb Rubber Asphalt

Abstract: Low-temperature cracking is one of the major pavement distresses in cold regions. To reduce the prevalence of such cracks, crumb rubber modified asphalt (CRMA) has been applied for a long time. However, CRMA experiences compatibility and segregation problems with asphalt. Silicone oil has long been seen to improve compatibility and segregation problems of polymers in asphalt, but its benefits on low temperature performance of crumb rubber asphalt have not been explored. Furthermore, silicone oil can be obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…FTIR spectroscopy is the most frequently used tool to observe the changes in the chemical structure of bitumen after ageing and measure the oxidation products. FTIR gives precise information regarding oxygenation rate, aliphaticity, and aromaticity [28]. The FTIR spectroscopy was conducted using the instrument: Perkin-Elmer Spectrum BX series Fourier transform infrared spectrometer (FT-IR), equipped with a Miracle ATR accessory.…”
Section: Materials and Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…FTIR spectroscopy is the most frequently used tool to observe the changes in the chemical structure of bitumen after ageing and measure the oxidation products. FTIR gives precise information regarding oxygenation rate, aliphaticity, and aromaticity [28]. The FTIR spectroscopy was conducted using the instrument: Perkin-Elmer Spectrum BX series Fourier transform infrared spectrometer (FT-IR), equipped with a Miracle ATR accessory.…”
Section: Materials and Experimental Methodsmentioning
confidence: 99%
“…This result presented to concluded that adding wax and rubber to neat bitumen increases the aromatic content significantly. Lushinga et al [28], have concluded that the higher content of aromatic components increases the resistance to crack at low temperatures. Therefore, the high aromatic content improves low-temperature cracking performance and that inducted the binder has low temperature sensitivity [24,31].…”
Section: Ftri Analysismentioning
confidence: 99%
“…This result concluded that adding wax and rubber to neat bitumen increases the aromatic content significantly. Lushinga et al (2019) and Zhang et al (2019) have concluded that the higher content of aromatic components increases the resistance to crack at low temperatures. Therefore, the high aromatic content improved low-temperature cracking performance and that indicated the binder has low-temperature sensitivity (Ghasemi and Marandi 2013, Taherkhani and Afroozi 2016, Yaacob et al 2016.…”
Section: Ftir Analysismentioning
confidence: 99%
“…AR can solve the environmental issues arising from the waste tires and improve the road performance of asphalt by using the effective properties of CR particles [4,5]. Currently, researchers are focusing more on the modification mechanism and production formula of AR [4][5][6][7][8][9], and there is little research on the evaluation system of AR. Hence, the evaluation system has not been unified for AR around the world.…”
Section: Introductionmentioning
confidence: 99%